An analysis of the wool characteristics that determine wool price for Merino wool in South Africa - M. Zenda; P.J. Malan; A.C. Geyer (Scientific African, 2024)
Globally, wool characteristics determine wool price. As a result, wool that does not match the standards for fibre diameter, clean yield and staple length at auctions are sold at cheaper prices. At global level, very few studies in the literature of wool characteristics that determine wool price have attempted to evaluate the actual percentage of clean yield that is required at a wool auction. The actual percentage of clean yield that is required at the wool auction for Merino wool is important to consider for methods that can be applied to improve clean yield. The objective of this study was to investigate the effect of wool characteristics (fibre diameter, clean yield and staple length) on the determination of Merino wool price in South Africa. The data of wool prices from 2009 to 2019 wool seasons was used for analysis. A multiple regression analysis of price (Rand/kg) of Merino wool was applied to three variables (fibre diameter, clean yield and staple length). Taken each variable separately, fibre diameter, clean yield and staple length made a statistically significant (p < 0.05) contribution to the determination of wool price, after controlling all other independent variables. Considering each variable separately, a one unit (µ) increase in fibre diameter was associated with a 30.236 unit decrease in wool price (Rand/kg). A one decimal unit increase in clean yield (%) was associated with 1.353 unit increase in wool price (Rand/kg). A one unit (mm) increase in staple length was associated with 0.912 unit increase in wool price (Rand/kg). The results indicated that clean yield is a challenge for Merino wool farmers. It is important that the Merino sheep breeds are shorn first at the shearing sheds to avoid contamination of wool with coloured fibres, kemp or crossbreed wool.